Safety and efficacy of lutein and lutein/zeaxanthin extracts from Tagetes erecta for poultry for fattening and laying (except turkeys). (15th May 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) evaluated (i) lutein from a saponified extract from Tagetes erecta obtained via extraction and saponification (lutein not less than 85% of total carotenoids (TC)) and (ii) lutein/zeaxanthin extract from Tagetes erecta obtained via extraction, saponification and isomerisation (lutein not less than 45% and zeaxanthin not less than 35% of TC). The maximum proposed use level of 80 mg TC from saponified Tagetes extract/kg complete feed for chickens for fattening and laying hens is safe for these animal categories. This conclusion can be extrapolated to minor poultry species for fattening and laying. The conclusions on saponified Tagetes extract for poultry for fattening and laying are extended to the saponified/isomerised Tagetes extract. The maximum use level of the saponified/isomerised Tagetes extract in breeding minor poultry should not exceed 50 mg TC/kg feed, considering the toxicological potential of zeaxanthin on reproduction. The saponified Tagetes extract is not genotoxic. This conclusion is extended to the saponified/isomerised Tagetes extract. Consumer exposure related to the consumption of animal products is very low compared to the exposure from other sources. The active substance is a viscous paste and may be irritant to skin and eyes; no exposure by inhalation is expected. In the absence of data, the Panel cannot conclude on the safety for the user of commercial preparations. The use of Tagetes extracts in poultry feed raised no concern for the environment. Tagetes extracts at levels up to the proposed maximum use level of 80 mg TC/kg complete feed have the potential to colour the egg yolk of laying hens and the skin of chickens for fattening. This conclusion is extended to minor poultry species for laying and for fattening. The use of the additive in feed and water for drinking is considered bioequivalent.